2007
DOI: 10.1093/europace/eum245
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy in left ventricular hypertrabeculation/non-compaction and myopathy

Abstract: CRT by biventricular pacing in LVHT, heart failure, and myopathy leads to improvement in functional capacity in all patients and improvement of systolic function in half of the patients. The weak response of LVHT patients to CRT may be due to inappropriate selection or comorbidities, in particular, neuromuscular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…It is also in contrast to epidemiological studies that found a worse prognosis when LBB was associated with dilated cardiomyopathy and myocarditis (22). This may be explained by the fact that LVHT patients with LBB responded well to cardiac therapy and, at least in some cases, to the cardiac resynchronization device (23). Furthermore, LBB was not associated with NMDs, which have been identified as indicators of a higher mortality rate.…”
Section: Discussioncontrasting
confidence: 59%
“…It is also in contrast to epidemiological studies that found a worse prognosis when LBB was associated with dilated cardiomyopathy and myocarditis (22). This may be explained by the fact that LVHT patients with LBB responded well to cardiac therapy and, at least in some cases, to the cardiac resynchronization device (23). Furthermore, LBB was not associated with NMDs, which have been identified as indicators of a higher mortality rate.…”
Section: Discussioncontrasting
confidence: 59%
“…One hundred sixteen of the 140 cases, diagnosed until October 2007, have been published previously [11][12][13][14]. The demographic and clinical baseline data of the included patients are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…CRT was even beneficial in a young child [88]. In a study on 102 LVHT patients, 8 had received a CRT system and all but one variably improved with regard to NYHA class, end-diastolic diameter, or systolic function [115]. If congestive heart failure does not even respond to CRT, heart transplantation (HTX) should be considered, which has been successfully carried out in a number of LVHT patients [19,116,117].…”
Section: Prevention Of Heart Failurementioning
confidence: 99%